2
$\begingroup$

I am trying to make this into a partial fractions form but i can't seem to find a way to do it.

The question is here:

Change into a partial fractions form.

\begin{align} \frac{2s}{(s+1)^2(s^2 + 1)} \\\\ \end{align}

i change to \begin{align} \frac{A}{(s+1)}+\frac{B}{(s+1)^2}+\frac{Cs+D}{(s^2+1)} \end{align}

I expand it and group like terms tgt but i am stump at this point \begin{align} 2s = (A+C)s^3 + (B+A+2C+D)s^2 + (A+C+2D)s + (B+A+D) \end{align}

Anyone can help?

$\endgroup$
3
$\begingroup$

Since you arrived to $$\begin{align} 2s = (A+C)s^3 + (B+A+2C+D)s^2 + (A+C+2D)s + (B+A+D) \end{align}$$ identification of the coefficients of the different powers of $s$ gives $$A+C=0$$ $$B+A+2C+D=0$$ $$A+C+2D=2$$ $$B+A+D=0$$ for which the solutions are easily obtained either using matrix or elimination and the final result is : $A=0$,$B=-1$,$C=0$ and $D=1$

$\endgroup$
  • $\begingroup$ You are very welcome ! $\endgroup$ – Claude Leibovici May 21 '14 at 9:43
  • $\begingroup$ @user152399 It's much easier to use Heaviside - see my answer. $\endgroup$ – Bill Dubuque May 21 '14 at 15:09
  • 1
    $\begingroup$ @BillDubuque. You are right but, by the end, Jyrki Lahtonen's solution is the fastest. Cheers. $\endgroup$ – Claude Leibovici May 22 '14 at 3:46
  • 1
    $\begingroup$ @Claude I meant easiest in general (ad-hoc methods don't generally apply). $\endgroup$ – Bill Dubuque May 22 '14 at 4:39
7
$\begingroup$

Such problems are easy using the Heaviside cover up method,. As I show in that answer, the method generalizes to quadratic denominators. Let's apply it to your problem.

$$\dfrac{a}{x+1} + \dfrac{b}{(x+1)^2} + \dfrac{cx+d}{x^2+1}\, =\, \dfrac{2x}{(x+1)^2(x^2+1)}\tag{E}$$

Multiplying $\rm\,(E)\,$ by $\,(x+1)^2,\,$ then evaluating at its root $\,x = -1\,$ yields

$$\ b\, =\, \dfrac{2x}{x^2+1}\Bigg|_{\large x\,=\,-1} =\, -1$$

Subtracting out this known summand leaves a fraction in partial form, so we are done:

$$\ \dfrac{2x}{(x+1)^2(x^2+1)}\, -\, \dfrac{-1}{(x+1)^2}\, =\, \dfrac{2x+x^2+1}{(x+1)^2(x^2+1)}\, =\, \dfrac{1}{x^2+1}\quad {\bf QED}$$

Remark $\ $ It is quite instructive to use the quadratic Heaviside method for all terms:

Multiplying $\rm\,(E)\,$ by $\,x^2+1\,$ then evaluating at its root $\,x = i\,$ yields

$$ \color{#0a0}c\, i + \color{#c00}d\, =\, \dfrac{2i}{(i\!+\!1)^2} \, =\, \dfrac{2i}{2i} \,=\, \color{#c00}1\,\Rightarrow\ \color{#0a0}{c = 0},\ \color{#c00}{d = 1} $$

Multiplying $\rm\,(E)\,$ by $\,(x+1)^2\,$ then evaluating at its root $\,x = w,\,$ so $\,\color{#c0d}{w^2\!+\!1 = -2w}$

$$a(w+1)+ b\, =\, \dfrac{2w}{\color{#c0d}{w^2\!+\!1}}\,=\,\dfrac{\ \ \,2w}{\color{#c0d}{-2w}} \,=\, -1\,\Rightarrow\ a=0\,\Rightarrow\, b=-1 $$

$\endgroup$
2
$\begingroup$

Hint: It is probably easiest to observe that $$ 2s=(s+1)^2-(s^2+1). $$ Use that in the numerator and see what you can cancel from the two terms you get.

$\endgroup$
  • $\begingroup$ Sorry, I just love spotting ad hoc tricks. $\endgroup$ – Jyrki Lahtonen May 21 '14 at 9:31
0
$\begingroup$

HINT:

Using Partial Fraction Decomposition formula, $$\frac{2s}{(s+1)^2(s^2+1)}=\frac A{s+1}+\frac B{(s+1)^2}+\frac{Cs+D}{s^2+1}$$

$\endgroup$
  • $\begingroup$ I tried it but i only am able to find B with Cover up rule. $\endgroup$ – Alex May 21 '14 at 8:38
  • $\begingroup$ @user152399, If you have four unknowns with four linear equations, right? $\endgroup$ – lab bhattacharjee May 21 '14 at 9:18
  • $\begingroup$ I don't understand what you mean. $\endgroup$ – Alex May 21 '14 at 9:23
  • $\begingroup$ @lab Using quadratic Heaviside is usually simpler than solving such systems of equations, see the Remark in my answer. $\endgroup$ – Bill Dubuque May 21 '14 at 15:44

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.